The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1124/mol.54.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Nonredox 5-Lipoxygenase Inhibitors Require Glutathione Peroxidase for Efficient Inhibition of 5-Lipoxygenase Activity

Abstract: Nonredox type 5-lipoxygenase (5-LO) inhibitors, such as ZM 230487, its methyl analogue ZD 2138, or the Merck compound L-739,010, suppress cellular leukotriene synthesis of ionophore stimulated granulocytes with IC 50 values of about 50 nM. However, in cell homogenates or in preparations of purified enzyme, up to 150-fold higher concentrations are required for similar inhibition of 5-LO activity. This loss of 5-LO inhibition in cell homogenates was reversed by addition of glutathione or dithiothreitol, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 32 publications
4
83
0
Order By: Relevance
“…Nonetheless, representatives out of this class such as the orally active compounds ZD 2138 5 or its ethyl analogue ZM 230 487 6 or L-739.010 8 are highly potent and selective for 5-LO in cellular assays [24]. We found that elevated peroxide levels and/or phosphorylation of 5-LO by MAPKAPK-2 and/or ERKs strongly impaired the potency of non-redox-type 5-LO inhibitors in activated PMNL [74], [75], [76].…”
Section: Molecular Pharmacology Of 5-lipoxygenase Inhibitorsmentioning
confidence: 86%
See 3 more Smart Citations
“…Nonetheless, representatives out of this class such as the orally active compounds ZD 2138 5 or its ethyl analogue ZM 230 487 6 or L-739.010 8 are highly potent and selective for 5-LO in cellular assays [24]. We found that elevated peroxide levels and/or phosphorylation of 5-LO by MAPKAPK-2 and/or ERKs strongly impaired the potency of non-redox-type 5-LO inhibitors in activated PMNL [74], [75], [76].…”
Section: Molecular Pharmacology Of 5-lipoxygenase Inhibitorsmentioning
confidence: 86%
“…It is still unclear if the bindingsite of these compounds is in fact the AA substrate-binding cleft in the active site. Thus, experimental data from molecular and biochemical studies suggest an allosteric mode of action [74]. Nonetheless, representatives out of this class such as the orally active compounds ZD 2138 5 or its ethyl analogue ZM 230 487 6 or L-739.010 8 are highly potent and selective for 5-LO in cellular assays [24].…”
Section: Molecular Pharmacology Of 5-lipoxygenase Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, experiments with ZM230487, a selective nonredox 5-LO inhibitor that blocks enzyme activity at low concentrations (Ͻ1 M) only in intact cells, 30 revealed that cell stressinduced 5-LO product formation occurred in intact cells and was not related to crude 5-LO activity after cell destruction (data not shown). …”
Section: Heat Shock and Osmotic Stress Lead To 5-lo Product Formationmentioning
confidence: 99%